6.15 - Mononuclear Ru/Os Compounds with η1 and C5–C6 Ligands - Gimeno, J.; Cadierno, V. (Comprehensive Organometallic Chemistry III, 13-Volume Set, 2007)
This chapter deals with the chemistry of η5- and η6-half-sandwich ruthenium and osmium complexes bearing η1-metal–carbon bonds. They belong to two types: (i) complexes with formally single σ-M–C bonds and (ii) complexes with MC (alkylidene and Fisher-type carbenes) and MC bonds (carbynes). Only a few examples have been described with η5- or η6-moieties different from the classical η5-Cp, η5-Cp* (or η5-indenyl), and η6-arene rings. This chemistry has attracted continuous interest during the last decade due to the well-known ability of the [M(η5- or η6-CnHm)L1L2] metal fragments to stabilize M–C bonds, enlarging the large information already reported in COMC (1982) and COMC (1995). To this regard, relevant developments are concerned with the availability of novel metal fragments used as precursors such as [M(η5-indenyl)L2], [OsCp(PPri3)2], or [OsX(η6-C6H6)L] among others. The great variety of ancillary ligands used has provided both electron-rich and -poor precursors allowing the access to appropriate metal fragments capable of being linked to a large series of hydrocarbon groups. These include not only classical alkyl, acyl, alkynyl, alkenyl, allenyl, and aryl groups, but also a large series of cyclometallated derivatives obtained through activation of alkyl and aryl C–H bonds. The chemistry of functionalized alkynyl complexes is especially relevant since they have been the subject of studies related to non-linear optical properties. On the other hand, the last decade has also witnessed remarkable progress in the chemistry of complexes containing carbene groups. Although these derivatives were well represented earlier, the discovery of systematic synthetic routes has given rise to a large series of novel alkylidenes [M]CR1R2 and cumulenylidenes [M]C(C)nCR1R2, which have been applied in numerous reactivity studies. This has disclosed novel entries to functionalized compounds bearing M–C and MC bonds through reactions with both nucleophiles and electrophiles including intra- and intermolecular cycloadditions. Derivatives containing previously unknown functionalized hydrocarbon and heterocyclic groups are presently accessible including α,β-unsaturated carbenes, polyalkenyl, polyenynyl, and a large series of bicyclic and tricyclic moieties among others. Novel synthetic approaches to carbyne complexes [M]CR have also been discovered, mostly involving η5-Cp–Os derivatives. Only a few examples of η6-arene osmium carbynes have been isolated to date.